DEVELOPING MATHEMATICS LEARNING MEDIA BASED STOP MOTION ANIMATION IN THE SUBJECT CIRCLE TANGENT FOR GRADE VIII JUNIOR HIGH SCHOOL - Vika Desti Wulandari; Edi Prajitno (Universitas Ahmad Dahlan, 2017)
The use of media in mathematics learning is used to assist students in understanding learning materials. The background of this development research is the absence of media that used in mathematics learning at SMP Muhammadiyah Seyegan and SMP Muhammadiyah Kasihan besides textbooks and worksheets as a learning resource. The purpose of this study was to develop learning media stop motion animation based on material tangent to the circle and to determine eligibility based on the assessment of experts and the students' responses. This research, the method used is Research and Development method. The subjects were expert lecturers, subject teachers, and students in grade VIII SMP and SMP Muhammadiyah Seyegan and SMP Muhammadiyah Kasihan. The object of this study is the learning media stop motion animation in the material tangent to the circle for grade VIII Junior High School. The stage of collecting data through direct observation, interviews, and questionnaires with research instruments such as questionnaires. The data analysis technique used is the analysis of qualitative data. The results showed that the developed learning media are included in the category of very decent (ideals percentage of 85.98%). Judging from the aspect of media, materials, and instructional media student responses are developed each get an average score of 89.5 respectively (criterion ideals 85.6%), 71.5 (percentage ideals 89.38%), and 57.85 (percentage ideals 82.64%). Thus mathematics learning media stop motion animation based on material circle tangent to class VIII SMP fit for use by students and teachers as a learning medium.